'Legal high' associated Wallenberg syndrome. (23rd May 2013) - Arora, Alok; Kumar, Anil; Raza, Muhammad Naeem
Abstract : 'Legal highs' are substances of synthetic or natural origin having psychotropic properties. 'Legal highs' are often new and, in many cases, the actual chemical ingredients in a branded product can be changed without notifications and the risks are unpredictable. Acute recreational drug toxicity is a common reason for presentation to both hospital and prehospital medical services. It appears that, generally, the pattern of toxicity associated with 'legal highs' is broadly similar to that seen with classical stimulant recreational drugs such as cocaine, MDMA (3, 4 methylenedioxy-N-methyl amphetamine) and amphetamine. Lack of clear literature pertaining to their chemical properties, pharmacology and toxicology makes an evaluation of their effects difficult. We describe a unique case in which consumption of such a substance led to hospital admission and a diagnosis of 'lateral medullary stroke' or 'Wallenberg syndrome'. We believe that this is the first described case of a 'legal high' intake linked to a posterior circulation stroke.